2015
DOI: 10.1016/j.jcps.2015.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Inspire me to donate: The use of strength emotion in donation appeals

Abstract: Previous research has shown that the use of negative emotions such as sadness in donation appeals can make people empathetic towards the donation target, increasing their tendency to donate (the “empathy‐helping” hypothesis). In this research we propose an “inspiration‐helping” hypothesis, and find that the positive emotion of strength can inspire people to donate. We show that combining the positive emotion of strength and the negative emotion of sadness is more effective as a means of persuading people to do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
94
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(105 citation statements)
references
References 28 publications
10
94
0
1
Order By: Relevance
“…However, Liang believes that when the fundraising information contains some positive emotional content, it can increase the individual's willingness to donate. When he discovers that the information contains positive emotional content with a strong sense of power, people's willingness to donate is enhanced, and when the donation information contains both the positive emotional content of the sense of power and the negative emotional content of sadness can more effectively persuade people to donate [9]. This result supports the inspiration-helping hypothesis.…”
Section: Literature Reviewmentioning
confidence: 62%
“…However, Liang believes that when the fundraising information contains some positive emotional content, it can increase the individual's willingness to donate. When he discovers that the information contains positive emotional content with a strong sense of power, people's willingness to donate is enhanced, and when the donation information contains both the positive emotional content of the sense of power and the negative emotional content of sadness can more effectively persuade people to donate [9]. This result supports the inspiration-helping hypothesis.…”
Section: Literature Reviewmentioning
confidence: 62%
“…Our results tended towards the opposite direction, though. This could be explained by recent research on the effect of strength emotions, which have shown to further increase a person's donation behavior [15]. We would argue however that the operationalization of evoking strength emotions in the latter research differs quite substantially from our setting.…”
Section: Conclusion and Discussionmentioning
confidence: 73%
“…It is observed that negative emotional appeals-in contrast to positive-generate a deeper analysis of the advertising message (Chang & Lee, 2009). Therefore, negative emotional appeals are considered an effective way to stimulate certain consumer intentions (Chang & Lee, 2009;Liang, Chen, & Lei, 2016) and lead to a greater intention to donate to charity, because they trigger consumer motivation to eliminate or reduce negative feelings (Anik, Aknin, Norton, & Dunn, 2011).…”
Section: Motivations For Donation and Purchase Of Cause-related Promentioning
confidence: 99%